Pengaruh Kualitas Konten dan Kepercayaan terhadap Keputusan Pembelian Produk terhadap Affiliate Marketing pada Penggunaan Shopee di Sungailiat - Oktariyanti Oktariyanti; Hengki Hengki (SENTRI: Jurnal Riset Ilmiah, 2026)
This study was conducted to determine the effect of content quality and trust on product purchasing decisions through Shopee affiliate marketing among users in Sungailiat. The research employed a quantitative approach with an associative method by distributing questionnaires to 106 active Shopee users in Sungailiat as research respondents. The collected data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, f-tests, and coefficient of determination analysis with the assistance of SPSS software. The findings revealed that content quality and trust had a positive and significant influence on purchasing decisions, both partially and simultaneously. The results also indicated that affiliate content that is informative, attractive, relevant, and credible can strengthen consumer confidence in making online purchases through the Shopee platform. This study is expected to contribute to the development of digital marketing research, especially in understanding consumer behavior on e-commerce platforms, and to provide insights for affiliates and business actors in developing more effective digital marketing strategies.